1986
DOI: 10.1002/food.19860300330
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic modification of egg‐white protein and some of its functional properties

Abstract: Because of the presence of proteinase inhibitors the enzymatic modification of egg-white protein demands a heating process to inactivate the inhibitors before enzyme action. The herewith occuring strong coagulation of the protein complicates the course of enzymatic hydrolysis. A laboratory process is given to produce partial hydrolyzates of egg-white protein using thermitase (a proteinase of Thermoactinomyces vulgaris) and pancreatin. To characterize the egg-white protein hydrolyzate the degree of hydrolysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Davis et al (2005) were able to relate a high foam yield stress of hydrolysed b-lactoglobulin (DH $ 15%) to high values of elastic modulus and essentially no viscous modulus, meaning that increased foam stabilization is promoted by an elastic interface of adsorbed proteins and peptides between the air and water phases. A study with egg albumen hydrolysed by pancreatin and thermitase showed a drastic increase in foaming capacity at DH up to $4%, after which the foam OR only increased slightly for DH up to $17% (Behnke et al, 1986). Foam stability was not significantly affected within this hydrolysis range, which is comparable with the present study on ovomucin foam stability.…”
Section: Foaming Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…Davis et al (2005) were able to relate a high foam yield stress of hydrolysed b-lactoglobulin (DH $ 15%) to high values of elastic modulus and essentially no viscous modulus, meaning that increased foam stabilization is promoted by an elastic interface of adsorbed proteins and peptides between the air and water phases. A study with egg albumen hydrolysed by pancreatin and thermitase showed a drastic increase in foaming capacity at DH up to $4%, after which the foam OR only increased slightly for DH up to $17% (Behnke et al, 1986). Foam stability was not significantly affected within this hydrolysis range, which is comparable with the present study on ovomucin foam stability.…”
Section: Foaming Propertiessupporting
confidence: 91%
“…Until now, the effect of hydrolysis on foaming properties of ovomucin has not been reported. However, enzymatic modification of whole egg albumen with pancreatin and thermitase (Behnke, Kiss, Nadudvari, & Ruttloff, 1986) or pepsin (Bamforth & Cope, 1987) apparently increases the foaming capacity of egg albumen. Furthermore, enzymatic hydrolysis of other proteins such as caseins (Panyam & Kilara, 1996), b-lactoglobulin (Davis, Doucet, & Foegeding, 2005;Ipsen et al, 2001), and a rapeseed isolate (Larre et al, 2006) also has resulted in altered foaming properties.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, there is a distinct relationship between the degree of hydrolysis (DH) and functional properties such as the distribution of molecular weights, surface hydrophobicity, solubility, foaming and emulsifying properties (Campbell et al 2003;Cigić & Zelenik-Blatnik 2004;Behnke et al 2006). However, the relationship between the DH and bioactivity of the peptides derived from egg white protein is not clear.…”
mentioning
confidence: 99%
“…Furthermore, it is considered to be a multi-purpose ingredient that imparts multiple functional properties such as gelling, foaming and emulsification in many food products, in addition to their nutritional quality [9]. However, its wider commercial use as protein supplements is limited due to allergenicity, insufficient digestibility, thermolability and high viscosity [10].…”
Section: Introductionmentioning
confidence: 99%